1998
DOI: 10.1038/bjc.1998.318
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic rate and S-phase fraction as prognostic factors in stage I cutaneous malignant melanoma

Abstract: the most significant predictors of recurrence-free (RFS) and overall survival. In Cox's multivariate analysis, tumour thickness (P = 0.0021), bleeding (P = 0.01 06) and MN index (P = 0.0058) predicted poor RFS in the 259 patients available for the analysis. Poor overall survival was predicted by MAI (P = 0.0002), bleeding (P = 0.004), SPF (P = 0.009) and male gender (P = 0.034). The present results indicate that mitotic activity index (MAI), volumecorrected mitotic index (MN index) and S-phase fraction (SPF) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 40 publications
2
18
0
3
Order By: Relevance
“…Results (mean and s.e.m.) are presented as a percentage of the total cells adhering after incubation with media alone Proliferation of abnormal melanocytes/melanoma cells is important for early tumour development and subsequent tumour progression, and the rate of proliferation (as measured by the mitotic index, S phase fraction, and percentage Ki67 positivity) is recognized as an important prognostic factor in this neoplasm (Moretti et al, 1990;Ramsay et al, 1995;Karjalainen et al, 1998). Previous research has shown that aMSH (and aMSH analogues) can suppress melanoma cell proliferation (Legros et al, 1981;Jiang et al, 1995;Smalley and Eisen, 2000), but our results demonstrate an aMSH-induced reduction in proliferation in the wild type MC1R transfected cell lines, whereas this decrease in cell numbers was not observed in the variant MC1R transfected melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Results (mean and s.e.m.) are presented as a percentage of the total cells adhering after incubation with media alone Proliferation of abnormal melanocytes/melanoma cells is important for early tumour development and subsequent tumour progression, and the rate of proliferation (as measured by the mitotic index, S phase fraction, and percentage Ki67 positivity) is recognized as an important prognostic factor in this neoplasm (Moretti et al, 1990;Ramsay et al, 1995;Karjalainen et al, 1998). Previous research has shown that aMSH (and aMSH analogues) can suppress melanoma cell proliferation (Legros et al, 1981;Jiang et al, 1995;Smalley and Eisen, 2000), but our results demonstrate an aMSH-induced reduction in proliferation in the wild type MC1R transfected cell lines, whereas this decrease in cell numbers was not observed in the variant MC1R transfected melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…115 J AM ACAD DERMATOL VOLUME 52,NUMBER 5 tumor-infiltrating lymphocytes). For example, tumor thickness and mitotic rate reflect the degree of cellular proliferation, a process representing the balance between cell birth (eg, growth fraction [139][140][141][142] and cell death (apoptosis) influenced by cell-cycle regulatory proteins (eg, loss p16 INK4a and apoptotic regulatory proteins 143,144 [eg, loss of apoptotic protease activating factor-1 145,146 ]). Tumor thickness is also influenced by the degree to which tumor cells can invade the dermis and maintain an adequate blood supply, processes governed by proteolytic enzymes (eg, matrix metalloproteinase [MMP]-2 expression [Gelatinase A]), 147 intercellular adhesion molecules (eg, gain of N-cadherin expression and loss of E-cadherin expression), and angiogenic growth factors/angiogenesis (eg, expression of VEGF).…”
Section: Potential Prognostic Molecular Markers In Primary Cutaneous mentioning
confidence: 99%
“…98 Mitotic rate and S-phase fraction proved to correlate independently with survivorship in one multivariate analysis. 99 Lymph node status and the sentinel lymph node biopsy Survival from melanoma drops progressively from 90% at 10 years for Stage I to 10% at 10 years for Stage IV disease. The major independent variable predicting survivorship in thick (ie 44.0 mm in depth) melanoma is the presence or absence of micrometastatic disease in the sentinel lymph node.…”
Section: Ulcerationmentioning
confidence: 99%